The epidemiology of mouth cancer: a review of global incidence - Moore, SR; Johnson, NW; Pierce, AM; Wilson, DF (Oral diseases, 2000)
Mouth cancer (143–145 ICD‐9) is a major health problem in many parts of the world. While its incidence is relatively low in most western countries there are some important exceptions to this trend: on the Indian subcontinent and in other parts of Asia it remains one of the most common forms of cancer. This review article summarises the global incidence of mouth cancer using cancer mapS. Data have been compiled from the latest edition of Cancer Incidence in Five Continents and recent studies from various locations around the world. Significant geographic variation is noted in the incidence of mouth cancer, with high rates reported for the Indian subcontinent and parts of Asia (male incidence rates in excess of 10 per 100 000 per annum). It is also noted that as with other forms of oral cancer, the majority of population‐based data for mouth cancer comes from the Western world with a paucity of reliable data from the so‐called developing countrieS. Mouth cancer remains a serious health problem in many parts of the world with many regions reporting increasing incidence rates particularly in maleS. Ongoing research into the aetiologic risk factors associated with this disease must remain a very high priority if the causes of mouth cancer are to be established and disease control protocols introduced widely.